Quality Improvement in Vegetable Greenhouse by Cadmium Pollution Remediation - Zhihui Yu; Jie Tang (Journal of Food Quality)
Greenhouse vegetable production (GVP) has grown in importance as a source of public vegetable consumption as well as income for farmers. Due to the high cropping index, substantial agricultural input, and confined environment, numerous contaminants can accumulate in GVP. Polluted soil is treated with metal cadmium pollution remediation technology in order to improve the quality of vegetable greenhouse soil and increase crop yields. The heavy metal cadmium-contaminated soil in vegetable greenhouses is rectified utilizing three methods: chemical remediation, bioremediation, and physical remediation. Soil restoration with broom sedge planting might result in a 9.78 percent reduction in cadmium pollution. Planting broom sedge has a root > stem > leaf effect on pollution remediation. The elimination of cadmium from the soil around the anode can be as high as 75.1 percent. The clearance rate of the soil near the anode was 75.1 percent and 77.9 percent, respectively, when the anode cadmium mass fraction dropped fast. Hence this paper focuses on the reduction of cadmium pollution to improve the quality of GVP crop to yield more benefit. Chemical leaching is faster, more efficient, and less dangerous, with a higher application value. The approach of bioremediation is of low cost and creates no secondary contaminants. Physical electrodynamics is easy to understand and has a distinct effect.